2014
DOI: 10.3186/jjphytopath.80.222
|View full text |Cite
|
Sign up to set email alerts
|

All-season detection of Satsuma dwarf virus using an immunochromatographic assay kit.

Abstract: IWANAMI, T. 7 (2014). All-season detection of Satsuma dwarf virus using an immunochromatographic assay kit. Jpn. J. Phytopathol. 80: 222-228.Satsuma dwarf virus (SDV) causes serious damage to citrus production by reducing the quality and yield of fruit. SDV in young shoots of citrus trees is usually detected using an enzyme-linked immunosorbent assay (ELISA); however, such tests can only be performed during several weeks in the spring and are time-consuming. To overcome these issues, we developed an all-seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The appearance of the control line and the test lines indicated a positive result (Kato et al, 2014;Kusano et al, 2007).…”
Section: Isolation and Identification Of Viruses From Citrus Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of the control line and the test lines indicated a positive result (Kato et al, 2014;Kusano et al, 2007).…”
Section: Isolation and Identification Of Viruses From Citrus Treesmentioning
confidence: 99%
“…We collected the shoots from citrus trees exhibiting symptoms of satsuma dwarf disease, such as leaf atrophy and loss of vigor. If shoots could not be collected, we followed the method of Kato et al (2014) and tested the flavedo of the fruit.…”
Section: Isolation and Identification Of Viruses From Citrus Treesmentioning
confidence: 99%
“…One drawback of ELISA is the need for expensive equipment (e.g., microplate reader), many reagents, time, and skilled technicians, where, in contrast, an immunochromatography test is very simple and can be performed by anyone, including nursery workers and farmers. An immunochromatography test kit for SDV, remarkably enabling the all-season diagnosis of SDV using young shoots and flower buds in the spring, fruit rinds in the summer and autumn, and the rinds of stored fruit and sprouts from scions in the winter (Kato et al 2014), was developed (Kusano et al 2007, Iwanami 2010 and used for detecting the virus under field conditions (Kato et al 2014). Furthermore, a recent report suggested that the immunochromatography test kit for SDV is more suitable for large-scale diagnoses than a DAS-ELISA (Kato et al 2020).…”
Section: Diagnostics (1) Elisa and Immunochromatography Testmentioning
confidence: 99%
“…We collected the shoots of citrus trees that showed symptoms of satsuma dwarf disease, such as leaf atrophy and loss of vigor. When shoots could not be collected, we followed the method of Kato et al (2014) and tested the avedo of fruit.…”
Section: Isolation and Identi Cation Of Viruses From Citrus Treesmentioning
confidence: 99%